The supervised internship: significant factors that influence the action of mathematics graduates in the city of Fortaleza/CE (Research, Society and Development, 2020)
The supervised internship is a moment of complex nature and several factors that are inserted in the action carried out by graduates/interns. The objective study presents some of the synthesized results of the master's thesis concluded in 2018, which determine factors that influence the supervised internship in mathematics degree courses in the city of Fortaleza/CE, based on the action performed by a sample of 169 interns/graduates. As for methodological procedures, its approach is pure, quantitative and exploratory. The results showed a good quality level/composition of the evaluation scale with 17 items measured on a LIKERT scale (Cronbach's α equal to 0.845 and total item statistics above 0.30); in the exploratory factor analysis, a factorial structure was evidenced, formed by 5 factors that explain 66, 6% of the total variation; in the linear regression studied there was a greater influence of specific mathematics subjects in relation to the other 4 factors.